RESPON PERTUMBUHAN DAN HASIL KACANG PANJANG (VIGNA SINENSIS, L) TERHADAP PUPUK ORGANIK DAN PUPUK DAUN - Osten M. Samosir; Gani Tambunan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
This study aims to determine the response of growth and yeild of long beans (Vigna sinensis L) to organic and foliar fertilizier, was conducted in jalan Bunga Ncole XXX No. 4, Medan, located at a height of ±28 m above sea level, which started from May to August 2020. This research used a Completely Randomized Block Design (CRBD) factorial, consist of two (2) teatment namely; organic fertilizer dosage consisting of 3 levels: P0 = 0 g/plot, P1 = 10 g/plot, and P2 = 20 g/Plot and liquid fertilizer consentration (A) consisting of 3 levels: A1 = 2,5 cc/l air, A2 = 5 cc/l air, and A3 = 7,5 cc/ l air. The results showed that the treatment of doseges of organic fertilizer up to 20 g/plot had a significant effect on the pod height did not significant effect on the number of pods per plant, productive branch number, total production per plot, average production per harvest, per plant, total production per plant, number of pods per bunch. Treatment of foliar fertilizer up to 7,5 cc/l of water had no significant effect on the number of pods per plant, pod length, branch number productive, total production per plot, average production per harvest, production per plant, total production per plant, number of flowers per plant, number of pods per bunch. The interaction between doses of Golden Guano solid organic fertilizer and Bayfolan foliar fertilizer had a significant effect on the pot height of long beans but hat not significant effect on the number of pods per plant, branch number productive branches, total production per plot, average production per harvest, production per plant, total production per plant, number of flowers per plant, number of pods per plant.